The physiological characteristics of zebra fish (Danio rerio) based on metabolism and behavior: A new method for the online assessment of cadmium stress. (October 2017) - Qi, Luhuizi; Ma, Jingchun; Song, Jie; Li, Shangge; Cui, Xiaoru; Peng, Xiaojing; Wang, Weiliang; Ren, Zongming; Han, Mei; Zhang, Ying
Abstract: In order to illustrate heavy metal ecotoxicology associated with interactions between chemicals and biological systems, we investigated physiological changes (metabolism and behavior response) of zebra fish ( Danio rerio ) under 48 h Cadmium chloride (CdCl2 ) exposure using online monitoring technique. The concentrations of CdCl2 were designed as 4.26, 42.6 and 85.2 mg/L, which were 0.1, 1.0, and 2.0 based on toxic unit (TU), respectively. The metabolism was assessed using the oxygen consumption (OC), and the behavior response was analyzed in behavior strength (BS). Significant inhibition of both OC and BS could be observed: OC was 617.39 ± 30.48 mg/kg/h in the control, and it decreased rapidly to 229.07 ± 28.66 mg/kg/h in 2.0 TU treatment. BS changed from 0.76 ± 0.07 (control) to 0.39 ± 0.04 (2.0 TU) with the increase of exposure concentrations. Further results suggested that both factors were related to diurnal variation during 48 h exposure, which could be regarded as circadian rhythms: the average values of OC and BS during photo-phase were significantly higher than both during scoto-phase in CdCl2 treatments ( p  < 0.05). After integrated analysis, the original values of both OC and BS with wide fluctuation showed a negative linear relationship with CdCl2 concentration. The levels of both OC and BS were positively correlated with CdCl2 ( r =  0.93 and p  < 0.01). It is suggested that both OC and BS provide an objective ground for CdCl2 stress assessment, and that also could be applied to test the changes of organisms quantitatively in toxic physiology. Highlights: Online metabolism and behavior analysis provide a ground for environmental stress assessment. Both physiological factors are related to diurnal variation in different treatments. OC and BS have a high correlation with extreme significance in cadmium exposure.